An Ethnolinguistic Analysis of the Meaning and Cultural Features of the Idiom “Deluu idvel delbe nirge” - Luvsantseren, Tserenchimed (Mongolian Journal of Humanities and Social Sciences, 2024)
This article seeks to analyze the meaning and cultural significance of the idiom ˈde.lʊː ˈit.wəl ˈdel.pə ˈnir.ɡɛ a commonly discussed expression among Mongolians, along with its variants, using ethnolinguistic theory and methodology. The scope of this study is defined by a focus on this idiom and related expressions. Our analysis is based on field study notes collected by ethnographers, records of Mongolian customs, and examples from dictionaries, all of which are essential for testing our hypothesis through comparison and synthesis of the available data. By examining specific linguistic phenomena, we can find insights into the culture, historical events, political relationships, and oral traditions that shape ethnic groups. In exploring national and ethnic languages through an ethnolinguistic lens, we focus on the interplay between linguistic and non-linguistic factors. Indeed, non-linguistic influences, such as the historical origins and history of the ethnic group are especially significant in elucidating the meaning and cultural characteristics of the idioms under study. This study draws on research materials, dictionaries, ritual glossaries, and prior studies on the topic of taboo, supplemented by case studies focusing on ethno-linguistic communication. There is a pressing need to examine specific linguistic and dialectal phenomena from an ethnolinguistic perspective. Future research should aim to explore the customs and traditions related to the concept of ‘spleen’ across various regions, not merely through the lens of idiomatic expressions, but to identify both the unique and shared characteristics of ethnic cultures. “Дэлүү идвэл дэлбэ ниргэ...” хэлц үгийн утга, соёлын онцлогийг угсаа хэл шинжлэлийн үүднээс тайлбарлах нь Хураангуй: Монголчуудын хэл, аялгуун дахь хэлц үг, тогтвортой нэгжийн олонх нь нүүдлийн соёл, мал аж ахуйгаас үүдэлтэй заншил, зан үйлд хамаардаг. Мөн угсаатны гарал, овгийн нэрийг тайлбарласан домог, аман мэдээнд өгүүлсэнтэй холбогдох нь байна. Тус өгүүлэлд монголчуудын дунд түгээмэл хэлэлцдэг дурдсан хэлц үг, түүний хувилбарын утга, соёлын онцлогийг угсаа хэл шинжлэлийн онол, арга зүйгээр тайлбарлав. Судалгааны хязгаарлагдмал талыг тус хэлц үгийн хүрээгээр тогтоож, угсаатны зүйчдийн цуглуулсан хээрийн шинжилгээний тэмдэглэл, монголчуудын зан заншлын тайлбар толь бичгийн баримт, зарим аман мэдээнд тулгуурлалаа. Монгол угсаатны зарим овог (хамниганы жишээгээр)-ийн эдийн соёл, оюуны соёлын илрэл болох шүтлэг бишрэл, угсаатны соёл-заншлын аман домгийн холбооноос хэвшиж тогтсон үг, хэллэг эдүгээ гол төлөв цээрлэх ёс, бэлгэдлийн утга илэрхийлдэг хэлц үг болж дэлгэрсэн нь судалгааны ажиглалт, үр дүнгээс харагдав. Түлхүүр үг: угсаатны хэл-соёл, цээрийн ёс, нүүдлийн ахуй соёл, угсаатны овгийн нэр